Renin-angiotensin system in lung tumor and microenvironment interactions - Catarata, MJ (2020)
The mechanistic involvement of the renin-angiotensin system (RAS) reaches beyond cardiovascular physiopathology. Recent knowledge pinpoints a pleiotropic role for this system, particularly in the lung, and mainly through locally regulated alternative molecules and secondary pathways. Angiotensin peptides play a role in cell proliferation, immunoinflammatory response, hypoxia and angiogenesis, which are critical biological processes in lung cancer. This manuscript reviews the literature supporting a role for the renin-angiotensin system in the lung tumor microenvironment and discusses whether blockade of this pathway in clinical settings may serve as an adjuvant therapy in lung cancer.